Проблема дихотомії публічних цінностей у західній теорії публічного управління - (:unkn) unknown (Національний лісотехнічний університет України, 2023)
The article considers the problem of dichotomy of public values in the Western Anglo-Saxon political and legal tradition. The difference between the existing views on it in the national science is explained. In this regard, the author provides an etymological analysis of key terms and a historical overview of the background of the problem. The author analyses the axiological schemes of public administration: M. Moore's (strategic triangle model), T. Jorgensen and B. Bozeman's (model of value contexts), and E. Whitesman's (dynamic model of public values). The article proves the relevance of studying the problem of the dichotomy of public values and public assessment processes. In our opinion, this is due to the dependence of any governance system on value coordinates – the fact that values largely determine how a modern state can organise the governance process, increase the manageability and competitiveness of its institutions. Moreover, this dependence allows society to form (cyclically/acyclically) a system of social values on the basis of which the state carries out public administration practices. The following have been determined: a) Public value (in the context of New Public Management) is a product created not so much by the state as by society itself. In this case, the role of the state can be described as an executor of the will of the public. To a certain extent, this role can be compared to the role of the service sector, where the public is a consumer of services (client) and the state is a service provider (service); b) The model of E. Whitesman can hardly serve to unify the approaches of its predecessors. The researcher excluded the element of cyclicality from her scheme, which, in our opinion, achieves the opposite goal to the one she postulates. Instead of combining approaches, we have their multiplication, i.e. instead of one unified scheme, we get three separate models.
Розглянуто проблему дихотомії публічних цінностей у західній англосаксонській політико-правовій традиції та з'ясовано відмінність наявного у вітчизняній науці погляду на неї. З огляду на це здійснено етимологічний аналіз ключових термінів та історичний екскурс в передісторію формування проблеми. Проаналізовано аксіологічні схеми публічного управління: М. Мура (модель стратегічного трикутника), Т. Йоргенсена і Б. Боузмана (модель ціннісних контекстів), Є. Вайтсман (динамічна модель публічних цінностей). Доведено актуальність дослідження проблеми дихотомії публічних цінностей і процесів суспільного оцінювання. На нашу думку, вона зумовлена залежністю будь-якої системи управління від ціннісних координат – від цінностей істотно залежить те, як сучасна держава може організовувати процес управління, удосконалювати керованість та конкурентоспроможність своїх інститутів. Причому означена залежність дає змогу громадськості формувати (циклічне/ациклічне) систему публічних цінностей, на основі яких держава здійснює практику публічного управління. Визначено: а) Публічна цінність (у контексті напряму "New Public Management") – продукт, створений не стільки державою, скільки самим суспільством. При цьому роль держави можна охарактеризувати як виконавця волі громадськості. До певної міри це призначення можна порівняти з роллю сфери обслуговування, де громадськість – споживач послуг (клієнт), а держава – постачальник послуг (сервіс); б) Модель Є. Вайтсман навряд чи може достатньою мірою слугувати справі уніфікації підходів попередників. Дослідниця вилучила зі своєї схеми елемент циклічності, що, на наш погляд, досягає мети, протилежної тій, яку вона постулює. Замість об'єднання підходів маємо їх множення, тобто замість однієї уніфікованої схеми отримуємо три окремих моделі.